Outlines of physical geology - Longwell, Chester R. (J. Wiley & sons, inc.,Chapman & Hall, limited, 1941)
Physical Geology can help. This guide not only helps you understand how glaciation, running water, weathering, and erosion have formed the landscapes we see today. This book an invaluable reference for those who want to understand complex processes deep inside the earth like plate tectonics, volcanic activity, and mountain-building.